Relação entre o tipo de tratamento para fraturas de côndilo e o desenvolvimento das disfunções temporomandibulares - Serrão, Brunna Queiroz (2023)
The mandibular condyle undergoes remodeling throughout an individual's life. Despite being a natural process, this phenomenon can be enhanced by functional, pathological or traumatic factors. Cone-beam computed tomography (CBCT) allows morphological analysis of this structure at different moments of the patient's life. The focus of this study was to investigate the remodeling process of the mandibular condyle after condylar fracture treatment, in addition to assessing the risk of Temporomandibular Disorders (TMD). They were analyzed by 2 previously calibrated, independent and blinded evaluators; 136 CBCT; if divergent, a third evaluator performed the analysis. The images were divided into 3 groups, according to the conduct: surgical, conversational and control group. To assess TMD, the DC/TMD questionnaire was used. For CBCT, the condyles were classified as: A- Without Osteoarthritis, B-Undetermined for Osteoarthritis and C- Osteoarthritis, following the DC/TMD criteria. There was no difference in any of the TMD cases in relation to the type of treatment (p>0.05). There was a significant difference in relation to the type of diagnosis (p<0.001). A little more than 68% of patients undergoing surgical treatment had Osteoarthritis, while for cases treated conservatively it was 50% and for the control group 22.3%.